Pemuktahiran Data Pemilih Berkelanjutan Sebagai Perlindungan Hak Politik Warga Negara di Kabupaten Kotawaringin Timur - Palenewen, Jovano Deivid Oleyver (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2023)
In the general election, East Kotawaringin itself, one of the problems that often occurs is the problem in the voter list. Based on the theory of democracy and the implementation of continuous updating of voter data in the fulfillment of political rights in East Kotawaringin, the focus of the research focuses on how the implementation of sustainable voter updating is one of the means to fulfill the political rights of voters in East Kotawaringin. Qualitative research, the selection of informants in this study will use purposive sampling. Purposive sampling itself is a sampling technique used by qualitative researchers to recruit participants who can provide in-depth and detailed information about the phenomenon under study as well as through observation and information media. The results of the research obtained were that in East Kotawaringin, Komisi Pemilihan Umum carried out data updating with Peraturan Komisi Pemilihan Umum Nomor 6 Tahun 2021 Tentang Pemutakhiran Data Pemilih Berkelanjutan . This focuses more on the KPU as the executor of updates with the implementation of work every month, with advantages and disadvantages with no ad hoc duty in non-election stages. Coordination was also carried out well as one of the sticks for the successful implementation of data updating. The results also found that the Badan Pengawas Pemilu as a supervisory agency contributed to the supervision of updating data and several obstacles, such as Bawaslu having to carry out larval tests to the supervision carried out. Improved coordination, carried out massive socialization, as well as updating data on remote areas that were not reached by ad-hoc temporarily and the community contributed to self-data reporting. Keywords: General Election, Continuous Voter Data Updating, East Kotawaringin